Pengaruh Kepemilikan Manajerial, Non-Debt Tax Shield, Operating Leverage, Cash Holding dan Risiko Bisnis Terhadap Struktur Modal Pada Perusahaan Manufaktur : Keywords: Managerial Ownershi; Non-Debt Tax Shield; Operating Leverage; Cash Holding; Business Risk; Capital Structure - Henarani Claudia Erwan; Titis Puspaningrum Dewi Kartika (Jurnal Akuntansi, 2022)
The purpose of this study was to determine the effect of managerial ownership, non-debt tax shield, operating leverage, cash holding, and business risk on capital structure. In this study, managerial ownership is proxied by the calculation of managerial shares divided by outstanding shares, non-debt tax shield is proxied by depreciation divided by total assets, operating leverage is proxied by Degree Of Leverage (DOL), cash holding is proxied by the calculation of cash and cash equivalents, and business risk. proxied by EBIT divided by total assets. While the capital structure is proxied by the Debt Equity Ratio (DER). The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research sample was obtained from 193 manufacturing companies and the research period was for three consecutive years (2018-2020). The data analysis technique in this study used descriptive analysis, classical assumption test, and multiple regression analysis. The results showed that managerial ownership, non-debt tax shield, cash holding had a significant effect on capital structure. Meanwhile, operating leverage and business risk have no Significant Effect On Capital Structur.